Learning Strategies Preference of Iraqi EFL Learners (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2021)
The current study aims at investigating Iraqi EFL learners’ knowledge and preference of language learning strategies. Data are collected using two self-reported questionnaires; a background questionnaire and the Strategy Inventory for Language Learning (SILL, Oxford, 1990) with some modifications to meet the needs of this study. The following questions are asked: 1-Are students aware of the concept of LLS? 2- If yes, how much they know about it? 3- What are the kinds of LLS they employed in their learning? 4- What are their preferred strategies? The questionnaires are submitted to a total sample that consists of 77 students. The results show that 80.5% of the students have no knowledge whatsoever about LLS. The rest of them (19.5%) shows confused and mixed information. Moreover, the metacognitive strategies are the most often used strategies with the highest “often” percentage of 53.1%. Next is the cognitive and memory strategies of 43.2% & 40.2 percentages respectively. These highest rates show the most preferred strategies used by the students in our department. As for the frequency of use, the metacognitive strategies are still the preferred and most frequently used with a total percentage of 92.6%. Memory strategies hold the second position with a total percentage of 90%. The rest shows the same range of frequency except the effective strategies that fall behind by approximately 10% to 15% less than the rest.